The research aims to discuss and explain the impact of contemporary cultural dimensions presented by Hofstede, especially the recently introduced dimension of leniency versus restraint (IVRIndulgence versus restraint) and its impact on accounting conserva - طلال محمد علي الججاوي; ابتهاج اسماعيل يعقوب (Iraqi Journal for Administrative Sciences, 2024)
The research aims to discuss and explain the impact of contemporary cultural dimensions presented by Hofstede, especially the recently introduced dimension of leniency versus restraint (IVRIndulgence versus restraint) and its impact on accounting conservatism as one of the accounting values, and by adopting the analytical and deductive approach in interpreting and making comparisons between cultural environments. Varied and specific, which achieved (highest - lowest) score in the cultural dimension scale of leniency towards self-restraint (IVR), and was represented by the countries falling under the Anglo-Saxon culture - America, the Scandinavian countries, the countries of Eastern and Central Europe, and Iraq. The practice of accounting conservatism in the Iraqi environment was tested using the scale (Basu 1997). The research concludes that the economic units in the research sample practice accounting conservatism in their financial statements and that the cultural dimension of self-control (R) affects accounting conservatism based on the data of the Iraqi cultural environment in a more significant way than other cultural dimensions affecting the aforementioned environment.